Praxis Pendidikan Kritis dalam Pembentukan Kesadaran kader: Studi Atas Sekolah Pendidikan Kritis PMII Rayon Tarbiyah Purwokerto - Mohammad Nur Zamzam; Irham M Zuhair; Wahyu Tetuko; Aulia Syahrani (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the praxis of critical education implemented through the Critical Education School (Sekolah Pendidikan Kritis—SPK) of PMII Rayon Tarbiyah Purwokerto and its contribution to the development of cadres' critical consciousness. A descriptive qualitative approach was employed, with data collected through in-depth interviews, observations, and documentation involving the branch chairperson, cadre development officers, facilitators, and SPK participants. Data were analyzed using the Miles and Huberman interactive model and validated through source and technique triangulation. The findings indicate that SPK functions as an alternative educational space that integrates literacy culture, dialogical learning, critical reflection, and social action into the cadre development process. These practices foster critical thinking skills, social awareness, and transformative consciousness through the dialectical interaction of knowledge, organizational ideology, lived experience, and praxis. The study concludes that SPK contributes to developing intellectually capable cadres who demonstrate social responsibility and a strong commitment to social transformation.